The Role of Religious Figures (Kyai) in Enhancing Sharia Economics: A Sociological Marketing Perspective Review - Anwar, Moh Muhlis; Sudoto, Sudoto (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
The kyai holds the highest position in Madura society, performing as a regulator and coordinator of the community's social life from a religious perspective. In the context of sociological marketing science, the purpose of this study is to present a literature review that pictures the figure of kyai as an actual manifestation of sharia economic development in social society. This study used a literature review methodology to reinforce the presence of a marketing sociological feature within the kyai figure. According to the findings of the study, the figure of a kyai can become a social leader and influencer with all his roles through the dimensions of Imam's opinions, person-supervisor congruence, thereby increasing people's trust in kyai, comments, and social value orientation in society to achieve the intention (desire) to socialize the Sharia economics. The research implies that leveraging the influential role of kyai in Madura can significantly enhance the acceptance and implementation of sharia economics, fostering sustainable economic development aligned with religious and cultural values.